Active-Support Integrated Control Method for Renewable Energy Generation Voltage Source Converters - Tianfeng, Chu; Jun, Zhao; Pengwei, Zhao; Dianyang, Li; Gang, Liu; Zhaowei, Ling (Frontiers in Energy Research, 2022)
Aiming at the grid connection stability of renewable energy generation Voltage Source Converters (VSCs), an active support integrated control strategy is proposed in this article. First, the standard third-order model based on synchronous generator is established, and the renewable energy generation VSCs are equivalent to an approximate synchronous voltage source with the excitation system and speed regulation system. Second, an improved virtual impedance control is added on the basis of the model, which can reduce the impact of impulse current and improve the reactive power support capacity during fault by switching the virtual impedance during fault. At the same time, a virtual dual PSS control is added to the model, and the damping torque method is used to provide positive damping torque for the system and improve the oscillation suppression ability of the system. Finally, a simulation system is built to verify the correctness and effectiveness of the proposed control strategy.